ROLE OF INNOVATIONS IN PROVIDING REPRODUCTIVE PROCESS IN AGRO-INDUSTRIAL PRODUCTION (INNOVATIVE ECONOMY, 2020)
Honcharenko O.V., Masliaieva O.O. ROLE OF INNOVATIONS IN PROVIDING REPRODUCTIVE PROCESS IN AGRO-INDUSTRIAL PRODUCTIONPurpose. The aim of the article is theoretical and methodological substantiation of the innovation factor in the implementation of the reproduction process in agro-industrial production.Methodology of research. The methodological basis of the study is a systematic approach to the study of the problems of innovative provision of the reproduction process in agro-industrial production. In the process of research, general scientific and special methods are used, in particular: monographic and system-analytical methods in substantiating the essence of the innovation process in agro-industrial production and in analyzing and evaluating trends in the development of agro-industrial production.Findings. Conflicting tendencies of development of agro-industrial production, which limit the innovative activity of agricultural producers, are established: reduction of reproductive abilities at the formal increase of the efficiency of agrarian production; deterioration of the material and technical and natural base condition with a relative increase in the volume of agriculture; the predominance of primitive production methods at many enterprises and the spread of intensive production technologies on individual ones; reducing the level of technological support in key industries and introducing high-tech production only in certain industries; a decrease in the average level of development in many agrarian regions and the degradation of the countryside and high rates of development in certain regions; chronic low state support to agriculture in the officially proclaimed priority of development of agricultural production.Originality. It is determined that the innovative process in agro-industrial production is a combination of scientific and technical, organizational, environmental and social changes taking place in the process of developing innovations and bringing them to implementation in agrarian production in order to increase its efficiency and obtain a qualitatively new competitive product. Given the content and peculiarities of the stages of the innovation process in agro-industrial production, it identifies 2 stages: 1) creation and assimilation of innovations; 2) the massive spread of innovation.The necessity of changing conceptual approaches to understanding the essence of innovation process and development of effective mechanisms of institutional regulation of innovation development is substantiated. It is established that at the present stage of development of agro-industrial production more productive is a wider approach to be found in the innovation policy and the use of the program-targeted approach.Practical value. The obtained results of the study deepen the practice of institutional regulation of innovation development and provide an opportunity to enhance the innovation process in agro-industrial production.Key words: agro-industrial production, innovation, innovative development, innovation policy, innovative strategy.
Keywords: Key words; agro-industrial production; innovation; innovative development; innovation policy; innovative strategy.